Comparison of Metformin plus Nicotinamide Solution with Kligman formula in the management of Melasma- a Clinical Trial in a Tertiary Care Hospital - Ahmed, Ishtiaq; Khan, Qamar-Ud-Din; Naeem, Uzma; Shabbir, Aysha; Khan, M Shahid; Ali, Umar Abdul (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare 30% Metformin plus 2% Nicotinamide solution with Kligman formula in the management of melasma in patients managed at tertiary care hospital of Rawalpindi. Study Design: Randomized controlled trial (ClinicalTrials.gov: NCT 05790577).Place and Duration of Study: Department of Dermatology, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Feb 2022 to Feb 2023.Methodology: A total of eighty-eight patients of melasma were recruited for this trial and allocated randomly into two groups: A and B. Group-A received the 30% metformin plus 2% nicotinamide solution while Group-B received the Kligman formula (fluocinolone acetonide 0.01%+ tretinoin 0.025% + hydroquinone 2%). Both groups were followed up for 12 weeks to look for response which was assessed on Melasma Area and Severity Index (MASI). MASI was calculated at the start of treatment, and at 4, 8 and 12 weeks. Adverse events such as itching and burning were noted and addressed at each visit.Results:  Out of eighty-eight patients, 66(75.0%) were females while 22(25.0%) were males. Mean age of the study participants was 30.93±7.94 years. Out of 44 patients in Group-A, 13(29.0%) showed mild improvement, 21(47.0%) patients showed moderate while marked improvement was seen in 4(9.0%) patients. In Group-B, out of 44 patients grade 1, 2, 3 and 4 improvements were seen in 14(31.81%) mild, 26(59.0%) moderate, 03(9.0%) marked and total improvement in one patient, respectively. Adverse effects were ....Conclusion: Both the treatment options used, 30% metformin with 2% nicotinamide solution and Kligman formula were equally efficacious in management of ..